Compliance To Pay Zakat on Gold: A Study on UUM Staff - fatihah adilah sukri (Global Review of Islamic Economics and Business, 2016)
Abstract: This paper aims to examine the relationship of attitude, religious value, knowledge on zakat, law of zakat as independent variable (IV) and compliance to pay zakat on gold as dependent variable (DV). A survey approach has been adopted in this study while the data are collected via structured questionnaires. The questionnaire was distributed to 250 respondents of  Muslim women staff among academician and non-academician from three colleges in Universiti Utara Malaysia (UUM), Sintok Kedah. In this study, the researchers developed a new construct in measuring the compliance to pay zakat on gold, knowledge on zakat and law of zakat. While, the construct in measuring attitude and religious value variable are borrowed from the previous study. The data are then quantitatively analyzed using SPSS program. The findings shows a high significant and  positive correlation between compliance to pay zakat on gold and knowledge on zakat followed by religious value, attitude and law of zakat. Further analysis using multiple regression analysis indicated that only knowledge on zakat, attitude and law of zakat give a significant and positive impact on zakat compliance payment on gold. The result of study contributed to the knowledge of zakat compliance. It is implied that the zakat authority need to intensify their efforts to further improve the effectiveness of education about zakat. Besides, it is proposed that zakat authority strives to cultivate a positive attitude of society towards zakat on gold using various strategic method.